Competitive interactions between whitefly- And aphid-transmitted poleroviruses within the plant host and the insect vectors - Henrique Bello, Vinicius [UNESP]; Ghosh, Saptarshi; Krause-Sakate, Renate [UNESP]; Ghanim, Murad (Scientific Societies, 2021)
Pepper cultivation in Israel has been constrained by two sympatric poleroviruses, Pepper vein yellows virus-2 (PeVYV-2) and Pepper whitefly-borne vein yellows virus (PeWBVYV), which are transmitted specifically by aphids and whiteflies, respectively. This study investigated the interaction between PeVYV-2 and PeWBVYV inside the host plant and the insect vectors. Our results show that PeVYV-2 and PeWBVYV compete against each other inside the host plant and also inside aphids. PeWBVYV was the weaker competitor inside the host plant, with diminished transmission rates when inoculated simultaneously or successively after PeVYV-2 and could only be transmitted efficiently when inoculated first and then challenged by PeVYV-2. Successive inoculations of plants with viruliferous whiteflies with PeWBVYV followed by viruliferous aphids with PeVYV-2 led to a coinfection rate of 60%, but with severely reduced titers of PeWBVYV in the coinfected plants compared with singly infected plants. In contrast, PeVYV-2 was the weaker competitor inside the insect vector, with reduced quantities of the acquired virus and a reduced transmission rate by aphids when given prior acquisition on PeWBVYV. However, we also show that the transmission efficiency of PeVYV-2 and PeWBVYV from coinfected plants by whiteflies and aphids remained comparable to that from singly infected plants. This is likely attributable to the reduced titers of PeWBVYV inside coinfected plants causing lesser impact on transmission of PeVYV-2 by aphids and the stronger competitiveness of PeWBVYV inside the whitefly. Competitive interactions between PeVYV-2 and PeWBVYV inside the host plant and insect vector can thus be beneficial for their coexistence.
Keywords: Aphid; Bell pepper; Coexistence; Coinfection; Competition; Molecular; Polerovirus; Single infection; Whitefly